Sound as affect: Difference, power and spatiality. (August 2016) - Gallagher, Michael
Abstract: This article considers what happens when sound is understood as affect. It begins by recounting a minor event in which sound moved my body. I use this as a starting point for defining sonic affect as the vibrational movement of bodies of all kinds, moving away from anthropocentric notions of sound based on human perception. The vibration of bodies can be understood as a 'base layer' of sound, which may activate or accrue layers of feeling, significance and meaning, but which is not reducible to them. Developing this conceptualisation of sonic affect, I argue that: (i) there are repeating affective tendencies of sound, but these unfold differently in context; (ii) sonic affect exercises power over bodies, sometimes by combining with meaning; and (iii) sound propagates affect through space in distinctive ways, some of which I discuss. These arguments are grounded in numerous examples, reflecting the variety of both sound and affect.